METODE TARJIH DALAM PENYELESAIAN HADIS MUKHTALIF (HADIS TENTANG WUDHU KARENA MENYENTUH KEMALUAN) - Shinta Ratu Putri Unon Purwanto; Athoillah Umar (IAIN Syekh Nurjati Cirebon, 2023)
This paper discusses the contradictory hadith about the invalidation of ablution when touching the private parts. It is not possible for one hadith to contradict another. In reality, the hadith that spread in the community are contradictory. The purpose of this paper is to provide an understanding of the contradictory hadith about the invalidation of ablution when touching the private parts. The method used is qualitative with a library research approach. The object of the research is the hadith narrated by Abu Dawud with index numbers 182 and 181 concerning ablution for touching the private parts. The results showed that in understanding the hadith narrated by Abu Dawud index numbers 182 and 181 which appear contradictory can be resolved using the tarjih method. The solution needs specification using the tarjih method by looking at the sanad. Both hadith are equally valid. Upon closer examination, both hadith have more authentic sanads. The conclusion of the study shows that these hadiths can be resolved using the tarjih method by looking at the sanad in light of existing considerations.